Motor empathy is a consequence of misattribution of sensory information in observers - Mahayana, Indra T.; Banissy, Michael; Chen, Chiao-Yun; Walsh, Vincent; Juan, Chi-Hung; Muggleton, Neil G. (Frontiers in Human Neuroscience, 2014)
Human behavior depends crucially on the ability to interact with others and empathy has a critical role in enabling this to occur effectively. This can be an unconscious process and based on natural instinct and inner imitation (Montag et al., 2008) responding to observed and executed actions (Newman-Norlund et al., 2007). Motor empathy relating to painful stimuli is argued to occur via the mirror system in motor areas (Rizzolatti and Luppino, 2001). Here we investigated the effects of the location of emotional information on the responses of this system. Motor evoked potential (MEP) amplitudes from the right first dorsal interosseus (FDI) muscle in the hand elicited by single pulses of transcranial magnetic stimulation (TMS) delivered over the left motor cortex were measured while participants observed a video of a needle entering a hand over the FDI muscle, representing a painful experience for others. To maintain subjects’ internal representation across different viewing distances, we used the same size of hand stimuli both in peripersonal and extrapersonal space. We found a reduced MEP response, indicative of inhibition of the corticospinal system, only for stimuli presented in peripersonal space and not in extrapersonal space. This empathy response only occurring for near space stimuli suggests that it may be a consequence of misidentification of sensory information as being directly related to the observer. A follow up experiment confirmed that the effect was not a consequence of the size of the stimuli presented, in agreement with the importance of the near space/far space boundary for misattribution of body related information. This is consistent with the idea that empathy is, at least partially, a consequence of misattribution of perceptual information relating to another to the observer and that pain perception is modulated by the nature of perception of the pain.